2018
DOI: 10.1038/s41380-018-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

Human brain arousal in the resting state: a genome-wide association study

Abstract: Arousal affects cognition, emotion, and behavior and has been implicated in the etiology of psychiatric disorders. Although environmental conditions substantially contribute to the level of arousal, stable interindividual characteristics are well-established and a genetic basis has been suggested. Here we investigated the molecular genetics of brain arousal in the resting state by conducting a genome-wide association study (GWAS). We selected N = 1877 participants from the population-based LIFE-Adult cohort. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…There is growing evidence that disregulation of arousal is associated with a variety of mental disorders such as depression, autism, and schizophrenia (Boutros et al, 2008;Razavi et al, 2013;Sander et al, 2016;Jawinski et al, 2019). In a genomewise association study, Jawinski et al (2019) found an association between resting-state vigilance levels (as assessed with EEG) and genetic markers for major depressive disorder, autism spectrum disorder, and Alzheimer's disease. In parallel, there has been widespread use of rsfMRI to study disease-related alterations in resting-state brain activity and connectivity.…”
Section: Vigilance and Diseasementioning
confidence: 99%
“…There is growing evidence that disregulation of arousal is associated with a variety of mental disorders such as depression, autism, and schizophrenia (Boutros et al, 2008;Razavi et al, 2013;Sander et al, 2016;Jawinski et al, 2019). In a genomewise association study, Jawinski et al (2019) found an association between resting-state vigilance levels (as assessed with EEG) and genetic markers for major depressive disorder, autism spectrum disorder, and Alzheimer's disease. In parallel, there has been widespread use of rsfMRI to study disease-related alterations in resting-state brain activity and connectivity.…”
Section: Vigilance and Diseasementioning
confidence: 99%
“…Such hyperarousal is a frequent finding in medicated and unmedicated patients with MD [ 24 , 25 , 26 , 27 ], and it has been shown to correlate with symptom severity in MD patients [ 27 ]. In addition, at the gene level, a genome-wide association study (GWAS) revealed significant evidence of an association of brain arousal with TMEM159, with other GWAS analyses and gene expression data suggesting a role of TMEM159 in MD [ 28 ]. Other indicators of hyperarousal in MD, such as prolonged sleep onset latencies [ 29 , 30 ], increased heart rate and skin conductance levels [ 31 ], or hyperactivity of the hypothalamic-pituitary-adrenal (HPA)-axis [ 32 ], are in line with the view that arousal may play a significant pathophysiological role in MD.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological data collection and processing was carried out as previously described (Jawinski et al, 2019(Jawinski et al, , 2015. EEG assessments were conducted according to a standardized operating procedure.…”
Section: Physiological Data Collection and Processingmentioning
confidence: 99%
“…The assessment of brain arousal was carried out as described elsewhere (Jawinski et al, 2019(Jawinski et al, , 2017. EEG-vigilance served as indicator for brain arousal and was measured using the Brain Vision Analyzer add-on VIGALL 2.1 (https://www.deutsche-depressionshilfe.de/forschungszentrum/aktuellestudien/vig all-vigilance-algorithm-leipzig-2-1; Hegerl et al, 2016).…”
Section: Assessment Of Brain Arousalmentioning
confidence: 99%